KEANEKARAGAMAN DAN DISTRIBUSI HERPETOFAUNA DI TAMAN WISATA ALAM DANAU BUYAN-TAMBLINGAN BALI - , IDA AYU ARI JANIAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Buyan-Tamblingan lakes Ecoturism Park consists of three types of ecosystem: 1) aquatic ecosystem such as lake, 2) terrestrial ecosystem such as forest, and 3) Artificial ecosystem such as forest plantation. The complete types of ecosystem usually indicated high level biodiversity. Herpetofauna could be used to indicator of ecosystem healthâs. Based on that statement, understanding the diversity and distribution of herpetofauna provides important information to the ecosystem condition. The aims of this study are to determine the diversity and distribution of herpetofauna and also to determine the habitat characteristics of herpetofauna in Buyan-Tamblingan lakes Ecotourism Park. The study was conducted at tourism area in tourist tracking line from Buyan Lake to Tamblingan Lake. Diversity and distributions data of herpetofauna was taken by using quadrat sampling method. The quadrat sampling was located systematically. Data collection on habitat characteristics of herpetofauna used nested sampling for biotic and circular plot for abiotic. The result showed, there are 11 species of herpetofauna consists of six species of amphibians and five species of reptiles. The diversity of herpetofauna in Buyan-Tamblingan lakes Ecotourism Park belongs to the intermediate categories (ID=1,43) of Shannon-Wiener Index. The Herpetofauna in this park has a clumped distribution pattern (Id= 3,25, GI= 0,024). The habitat characteristics of herpetofauna in this park were also different for each type of ecosystem.